Correction: Fernandes et al. Stress Granule Assembly Can Facilitate but Is Not Required for TDP-43 Cytoplasmic Aggregation. Biomolecules 2020, 10, 1367 - Nikita Fernandes; Luke Nero; Shawn M. Lyons; Pavel Ivanov; Telsa M. Mittelmeier; Timothy A. Bolger; J. Ross Buchan (Biomolecules, 2021)
In the original article [...]